Analisis user experience Honeycomb pada Platform Lazada - Naryapramono, Afrilza Daffa; Satria, Diva; Pambudi, Fawwaz Haryolukito; Fadhlullah, Muhammad Azzam; Rinandi, Tyto; Arini, Florentina Yuni (LP2M Institut Teknologi dan Bisnis ASIA Malang, 2025)
This paper aims to examine the User Experience (UX) on the Lazada e-commerce platform through the UX Honeycomb model. Enhancing the shopping experience, from finding items to completing purchases, is a crucial element for e-commerce platforms. In today's competitive e-commerce landscape, improving UX quality has become a key differentiator directly impacting user retention and satisfaction, especially for Lazada. The UX Honeycomb's seven aspects—useful, usable, desirable, findable, accessible, credible, and valuable—are essential for Lazada to maintain its market position and foster lasting customer relationships. This study gathered information from a survey of 50 participants. The survey revealed that Lazada's interface is considered usable due to its user-friendly design and various digital payment options. For the useful aspect, the product recommendation feature was found to be helpful for locating items that meet specific needs. However, the desirable aspect requires improvement, as Lazada's visual appeal was not considered engaging enough. The findable aspect is well-addressed by an efficient and straightforward search function. While the accessible aspect shows progress with an intuitive design, further support for users with physical or sensory impairments is needed. The credible aspect received positive feedback, with user reviews and comprehensive product descriptions building trust. Finally, the valuable aspect is evident through discount programs, vouchers, and flash sales that offer financial advantages. Therefore, the UX Honeycomb framework offers valuable insights into Lazada's continued efforts to create a seamless and fulfilling user experience.